Alginate inhibits iron absorption from ferrous gluconate in a randomized controlled trial and reduces iron uptake into Caco-2 cells. - Anna A Wawer; Linda J Harvey; Jack R Dainty; Natalia Perez-Moral; Paul Sharp; Susan J Fairweather-Tait (PLoS ONE)
Unlabelled Previous in vitro results indicated that alginate beads might be a useful vehicle for food iron fortification. A human study was undertaken to test the hypothesis that alginate enhances iron absorption. A randomised, single blinded, cross-over trial was carried out in which iron absorption was measured from serum iron appearance after a test meal. Overnight-fasted volunteers (n = 15) were given a test meal of 200 g cola-flavoured jelly plus 21 mg iron as ferrous gluconate, either in alginate beads mixed into the jelly or in a capsule. Iron absorption was lower from the alginate beads than from ferrous gluconate (8.5% and 12.6% respectively, p = 0.003). Sub-group B (n = 9) consumed the test meals together with 600 mg calcium to determine whether alginate modified the inhibitory effect of calcium. Calcium reduced iron absorption from ferrous gluconate by 51%, from 11.5% to 5.6% (p = 0.014), and from alginate beads by 37%, from 8.3% to 5.2% (p = 0.009). In vitro studies using Caco-2 cells were designed to explore the reasons for the difference between the previous in vitro findings and the human study; confirmed the inhibitory effect of alginate. Beads similar to those used in the human study were subjected to simulated gastrointestinal digestion, with and without cola jelly, and the digestate applied to Caco-2 cells. Both alginate and cola jelly significantly reduced iron uptake into the cells, by 34% (p = 0.009) and 35% (p = 0.003) respectively. The combination of cola jelly and calcium produced a very low ferritin response, 16.5% (p < 0.001) of that observed with ferrous gluconate alone. The results of these studies demonstrate that alginate beads are not a useful delivery system for soluble salts of iron for the purpose of food fortification. Trial registration ClinicalTrials.gov NCT01528644.